PENGARUH STORE ATMOSPHERE DAN SOSIAL MEDIA MARKETING TERHADAP KEPUASAN PELANGGAN PADA CAFE D’JAPOS DI PASANGKAYU - Muh Fauzi; Andi Amri (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to determine the influence of store atmosphere and social media marketing on customer satisfaction at Cafe D'japos in Pasangkayu. The type of research used is quantitative research. The population in this study were Cafe D'japos customers in Pasangkayu who made purchases. The sampling technique in this research was purposive sampling with a total of 75 respondents. The data collection technique used was a questionnaire, which was then processed using SPSS. The scale used in this research is a Likert scale with data analysis using multiple linear regression. The results of this research show that store atmosphere and social media marketing have a simultaneous and partial effect on customer satisfaction at Cafe D'japos in Pasangkayu.